Cholinergic modulation of striatal microcircuits - Abudukeyoumu, Nilupaer; Hernandez‐Flores, Teresa; Garcia‐Munoz, Marianela; Arbuthnott, Gordon W. (The European journal of neuroscience, 2019)
The purpose of this review is to bridge the gap between earlier literature on striatal cholinergic interneurons and mechanisms of microcircuit interaction demonstrated with the use of newly available tools. It is well known that the main source of the high level of acetylcholine in the striatum, compared to other brain regions, is the cholinergic interneurons. These interneurons provide an extensive local innervation that suggests they may be a key modulator of striatal microcircuits. Supporting this idea requires the consideration of functional properties of these interneurons, their influence on medium spiny neurons, other interneurons, and interactions with other synaptic regulators. Here, we underline the effects of intrastriatal and extrastriatal afferents onto cholinergic interneurons and discuss the activation of pre‐ and postsynaptic muscarinic and nicotinic receptors that participate in the modulation of intrastriatal neuronal interactions. We further address recent findings about corelease of other transmitters in cholinergic interneurons and actions of these interneurons in striosome and matrix compartments. In addition, we summarize recent evidence on acetylcholine‐mediated striatal synaptic plasticity and propose roles for cholinergic interneurons in normal striatal physiology. A short examination of their role in neurological disorders such as Parkinson's, Huntington's, and Tourette's pathologies and dystonia is also included. We review literature on striatal cholinergic interneurons: their synaptic and non‐synaptic release, afferents, and connectivity with the activation of pre‐ and postsynaptic cholinergic receptors and their role in the modulation of normal and pathological microcircuits. Drawings illustrate glutamatergic and dopaminergic afferents and magnified microcircuit with cholinergic interneuron (red) surrounded by GABAergic interneurons (different colors) and medium spiny neurons (green).